2020
DOI: 10.1016/j.chaos.2020.110156
|View full text |Cite
|
Sign up to set email alerts
|

An epidemic model SIPHERD and its application for prediction of the spread of COVID-19 infection in India

Abstract: Highlights A novel compartmental epidemic model SIPHERD is employed for COVID-19 prediction for India where it has reached at alarming level. Impact of lockdown and the number of tests conducted per day on predictions of containment is studied. Purely Asymptomatic cases and spread from them as well as Exposed in incubation period considered. Increasing the tests per day by 10k every day, stringent measures on social-distancing and strict… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 17 publications
0
35
0
Order By: Relevance
“…Despite the scarce information on the virus and the availability of insufficient data, the mathematical modelling community did not fail to produce efforts to assist the health authorities [10] , [11] . Many significant papers have been published, ranging from statistical approaches [12] , [13] , [14] , [15] , to deterministic compartmental models [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] to stochastic procedures [26] , [27] . Some aim to estimate the transmission risk [28] , others to estimate the number of unreported cases [29] , or to consider both the age and social contact structure [30] .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the scarce information on the virus and the availability of insufficient data, the mathematical modelling community did not fail to produce efforts to assist the health authorities [10] , [11] . Many significant papers have been published, ranging from statistical approaches [12] , [13] , [14] , [15] , to deterministic compartmental models [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] to stochastic procedures [26] , [27] . Some aim to estimate the transmission risk [28] , others to estimate the number of unreported cases [29] , or to consider both the age and social contact structure [30] .…”
Section: Introductionmentioning
confidence: 99%
“…Several models have recently been proposed and implemented in order to understand the dynamics of COVID-19. Most of these models are based on the traditional epidemiological model, called the susceptible-exposed-infectious-recovered (SEIR) model, which was introduced to study the pandemic transmission within a human community [4][5][6][7][8][9][10][11][12][13][14]. To date, very few attempts have been devoted to describe the interaction between the immune system and SARS-CoV-2 [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Lopez et al [4] used the modified SEIR model to predict the COVID-19 outbreak in Spain and Italy. Ashutosh et al [5] estimated pure asymptomatic infection cases based on a SEIR model. The results showed that infection may last for a long time without a vaccine.…”
Section: Introductionmentioning
confidence: 99%